Uji Validitas Isi dan Konstruk pada Pengembangan Instrumen Evaluasi Pembelajaran - Noviarni Taneo; Sarci Henukh (Educational Journal, 2026)
This study aims to describe the process of developing a learning evaluation instrument and to examine its quality in terms of content validity, construct validity, and reliability. The research employed the Research and Development (R&D) method, which consisted of several stages, namely needs analysis, blueprint development, item construction, expert validation, instrument revision, and field testing. Data were collected through validation sheets, questionnaires, and documentation. Content validity was analyzed using Aiken’s V index, construct validity was examined using Pearson’s Product Moment correlation, and instrument reliability was measured using Cronbach’s Alpha coefficient. The results revealed that the developed instrument demonstrated good quality. The content validity test indicated that most instrument items were categorized as valid to highly valid, with Aiken’s V values ranging from 0.61 to 1.00. The construct validity test showed that 9 out of 10 items were declared valid because their calculated correlation coefficients exceeded the critical value of the correlation table, while one item required revision. Furthermore, the reliability test yielded a Cronbach’s Alpha coefficient of 0.87, indicating that the instrument was reliable. These findings suggest that the developed learning evaluation instrument meets the criteria of a high-quality instrument, being both valid and reliable, and is therefore suitable for use as an evaluation tool in the learning process. The systematic development of the instrument contributes to more objective, accurate, and trustworthy measurement outcomes.